Calculation of DC Corona Wind - Žebrauskas, S.; Ramanauskas, A. (Elektronika ir Elektrotechnika, 2004)
Analytical-digital method of calculation the velocities of DC corona wind in wire-to-plain electrode system is discussed. Themethod is based upon an assumption that the electric field of the discharge is independent from the corona wind field, and, vice versa,this field is the function of electric field quantities of the discharge. Differential quantities of the electric field of DC corona dischargeare obtained analytically by using the Deutch‘s-Popkov‘s assumption of coincidence the directions of electrostatic field strength vectorand the field vector of corona discharge. The dependence of the force acting the elementary charge on the coordinates is essential andthe influence of any coordinate to the force must not be denied. The results of analysis of DC corona field differential quantities arechecked indirectly by comparison of theoretical and experimental voltampere characteristics. It‘s misalignment do not exceed 8 %. Theset of equations of corona wind represented by the Navier and Stokes equations and the equation of stream continuity are solved by useof finite difference method. The values of analytically determined components of spatial force acting the charge element in the nodes ofsquare net are being used in the process of iterative computation. Ill.3, bibl. 15 (in Lithuanian; summaries in Lithuanian, English andRussian).